Moral Education from the Perspective of Bertrand Russell (Raparin Journal of Humanities (RJH), 2026)
This paper sheds light on moral education based on Russell's ideas and explores the role of education and morality in society. The descriptive analytical method is used for .It also focuses on freedom of thinking as a foundation for developing morality. Russell follows a method that frees individuals' minds and develops critical and independent thinking as a foundation for emotional, physical, and social cognition in educating children.According to Russell, actual morality derives from an environment where independent thinking exists and allows individuals to develop a sense of responsibility guided by reason and empathy instead of being imposed by authority.The study, through a combination of philosophical ideas and modern practical education, proposes an opinion on how Russell's ideas can address current problems of moral education in the first six years of a child's development.According to Russell, moral education starts from birth until age six. In this study, we clarify the aspects that serve as a foundation for the child's moral education. These aspects are rooted in certain human emotions that actively participate in developing the child's physical and psychological well-being, which relates to their personality in the future.All in all, this trend in education focuses on a reasoned and logical framework for developing a responsible human personality from the perspective of moral education in the modern world.